Development of a Sagu Alu–Based Physical Education Learning Design to Enhance Elementary Students’ Motor Skills - Wani, Bernabas; Natal, Yanuarius Ricardus; Bate, Nikodemus; Mari, Anselmus A.; Fuzita, Mira (Universitas Islam Negeri Raden Intan Lampung, 2026)
Motor skill development is a core objective of elementary physical education, yet classroom practice often remains dominated by repetitive drills with limited integration of culturally relevant movement experiences. This study aimed to develop and evaluate a physical education learning design based on the traditional Sagu Alu game to enhance elementary students’ motor skills. The study used a Research and Development approach with the ADDIE model, comprising analysis, design, development, implementation, and evaluation. Participants were 30 students in Grades IV–VI at SD Citra Bakti selected through purposive sampling. Data were collected through expert-validation sheets, student-response questionnaires, classroom observation, and motor-skill tests administered before and after implementation. Descriptive statistics were used to summarize validation and practicality data, while learning improvement was examined using paired-samples comparison and normalized gain analysis. The developed product achieved very high expert validation scores, ranging from 91% to 92%, indicating strong content, media, and design feasibility. Student responses were also highly positive, with 88% for appearance, 86% for ease of use, and 90% for perceived effectiveness. Students’ mean motor-skill score increased from 57.5 on the pre-test to 81.5 on the post-test, and the mean N-gain was 0.56, which falls in the moderate improvement category. Overall, the findings indicate that the Sagu Alu–based learning design is feasible, practical, and instructionally promising for improving motor skills while simultaneously embedding local cultural heritage into elementary physical education.